Predictive values of stool-based tests for mucosal healing among Taiwanese patients with ulcerative colitis: a retrospective cohort analysis - Yen,Hsu-Heng; Chen,Mei-Wen; Chang,Yu-Yao; Huang,Hsuan-Yuan; Hsu,Tsui-Chun; Chen,Yang-Yuan (PeerJ, 2020)
Background/Purpose Over the past two decades, ulcerative colitis (UC) has emerged in the Asia Pacific area, and its treatment goal has shifted from symptom relief to endoscopic remission. Endoscopy is the gold standard for the assessment of mucosal healing; however, it is an invasive method. Fecal calprotectin (FC) is a non-invasive stool-based inflammatory marker which has been used to monitor mucosal healing status, but it is expensive. By contrast, the immune fecal occult blood test (iFOBT) is a widely utilized stool-based screening tool for colorectal cancer. In this study, we compared the predictive values of iFOBT and FC for mucosal healing in Taiwanese patients with UC. Methods A total of 50 patients with UC identified via the electronic clinical database of Changhua Christian Hospital, Taiwan, were retrospectively enrolled from January 2018 to July 2019. Results of iFOBT, FC level, and blood tests as well as Mayo scores were reviewed and analyzed. Colonic mucosa was evaluated using the endoscopic Mayo subscore. Results The average age of the patients was 46 years, and 62% of the patients were men. Disease distribution was as follows: E1 (26%), E2 (40%), and E3 (34%). Complete mucosal healing (Mayo score = 0) was observed in 30% of patients. Endoscopic mucosal healing with a Mayo score of 0 or 1 was observed in 62% of the patients. Results of FC and iFOBT were compared among patients with and without mucosal healing. Predictive cutoff values were analyzed using receiver operating characteristics curves. iFOBT and FC had similar area under the curve for both complete mucosal healing (0.813 vs. 0.769, respectively, p = 0.5581) and endoscopic mucosal healing (0.906 vs. 0.812, respectively, p = 0.1207). Conclusion In daily clinical practice, FC and iFOBT do not differ in terms of predictive values for mucosal healing among Taiwanese patients with UC.
Keywords: Ulcerative colitis; Chronic inflammatory disease; Fecal calprotectin; Occult blood test